PENGELOMPOKAN GENOTIPE PADA TANAMAN JAGUNG PULUT LOKAL (Zea mays L. var. ceratina) DENGAN SELEKSI TONGKOL KE BARIS - Tauhid, Yufa Indrawan; Murdono, Djoko (Percetakan Umi Toaha Makassar, 2024)
Waxy corn (Zea mays L. var. ceratina) is a food commodity that has a high amylopectin content of 72% and 28% amylose. Waxy cron still has weaknesses, namely low productivity reaching 2-2.5 tons/hectare, to overcome this problem research is needed to obtain the genotype of corn plants with high productivity. The purpose of this study was to obtain homogeneous genotype traits by selection of cobs to rows. The method used in this study is qualitative and quantitative descriptive with surveys in the field. The results of this study obtained the T-5 genotype which passed the selection for qualitative parameters, but quantitative parameters were still found to be diverse at the time of anthesis and the number of cobs. It is necessary to continue the selection for T-5, focusing on selection based on anthesis time, number of cobs, the average weight of whole cobs, and average total seed weight of 1 cob to obtain a homogeneous T-5 based on curative and quantitative parameters. Cob to Line Selection research based on qualitative and quantitative parameters has a high chance of immediately obtaining homogeneous genotypes are T-1, T-2, T-3, T-4, T-7, T-8, and T-10, while the opposite is T-6 and T-9